Study on the synthesis of sulfonamide derivatives and their interaction with bovine serum albumin. (13th June 2014) - Zhang, Xuehong; Lin, Yijie; Liu, Lina; Lin, Cuiwu
Abstract Three sulfonamide derivatives (SAD) were first synthesized from p‐hydroxybenzoic acid and sulfonamides (sulfadimidine, sulfamethoxazole and sulfachloropyridazine sodium) and were characterized by elemental analysis, 1H NMR and MS. The interaction between bovine serum albumin (BSA) and SAD was studied using UV/vis absorption spectroscopy, fluorescence spectroscopy, time‐resolved fluorescence spectroscopy and circular dichroism spectra under imitated physiological conditions. The experimental results indicated that SAD effectively quenched the intrinsic fluorescence of BSA via a static quenching process. The thermodynamic parameters showed that hydrogen bonding and van der Waal's forces were the predominant intermolecular forces between BSA and two SADs [4‐((4‐(N‐(4, 6‐dimethylpyrimidin‐2‐yl)sulfamoyl)phenyl)carbamoyl)phenyl acetate and 4‐((4‐(N‐(5‐methylisoxazol‐3‐yl)sulfamoyl)phenyl)carbamoyl)phenyl acetate], but hydrophobic forces played a major role in the binding process of BSA and 4‐((4‐(N‐(6‐chloropyridazin‐3‐yl)sulfamoyl)phenyl) carbamoyl)phenyl acetate. In addition, the effect of SAD on the conformation of BSA was investigated using synchronous fluorescence spectroscopy and circular dichroism spectra. Molecular modeling results showed that SAD was situated in subdomain IIA of BSA. Copyright © 2014 John Wiley & Sons, Ltd.